2013
DOI: 10.1073/pnas.1301445110
|View full text |Cite
|
Sign up to set email alerts
|

APE2 is required for ATR-Chk1 checkpoint activation in response to oxidative stress

Abstract: The base excision repair pathway is largely responsible for the repair of oxidative stress-induced DNA damage. However, it remains unclear how the DNA damage checkpoint is activated by oxidative stress at the molecular level. Here, we provide evidence showing that hydrogen peroxide (H 2 O 2 ) triggers checkpoint kinase 1 (Chk1) phosphorylation in an ATR [ataxia-telangiectasia mutated (ATM) and Rad3-related]-dependent but ATM-independent manner in Xenopus egg extracts. A base excision repair protein, Apurinic/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
149
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(158 citation statements)
references
References 73 publications
6
149
0
Order By: Relevance
“…Histone H3 was used as a loading control for chromatin-bound fractions. These observations suggest that Zf-GRF-stimulated 3′-5′ exonuclease activity of APE2 is important for the generation of RPA-ssDNA; assembly of the checkpoint protein complex including ATR, ATRIP, and 9-1-1 complex; and subsequent Chk1 phosphorylation by activated ATR (22). Similarly, WT APE2, but not the Zf-GRF R502E nuclease-deficient mutant, was able to rescue H 2 O 2 -induced Chk1 phosphorylation in APE2-depleted egg extracts (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Histone H3 was used as a loading control for chromatin-bound fractions. These observations suggest that Zf-GRF-stimulated 3′-5′ exonuclease activity of APE2 is important for the generation of RPA-ssDNA; assembly of the checkpoint protein complex including ATR, ATRIP, and 9-1-1 complex; and subsequent Chk1 phosphorylation by activated ATR (22). Similarly, WT APE2, but not the Zf-GRF R502E nuclease-deficient mutant, was able to rescue H 2 O 2 -induced Chk1 phosphorylation in APE2-depleted egg extracts (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Disruption of either the APE2 Zf-GRF DNA-binding surface or its PCNA-binding PIP box (22) compromises downstream chromatin recruitment of RPA, checkpoint kinases, and checkpoint activation (SI Appendix , Fig. S13); however, deletion or mutation of the APE2 Zf-GRF has no detectable impact on APE2 association with chromatin following oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of Chk1 and increased Rad22-YFP foci in wat1-null mutants, even in the absence of genotoxic stimuli, support our hypothesis. Since phosphorylation of Chk1 in response to H 2 O 2 has been reported recently (Willis et al 2013), and Wat1 is a major component of both the Tor2 and Tor1 complexes (TORC1 and TORC2), we speculated that it plays a role in the regulation of the oxidative stress response. We observed much reduced growth of wat1-deleted cells on plates containing H 2 O 2, indicating its role in the oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%
“…ATR is activated in response to stalled DNA replication forks (Nam and Cortez, 2011), which can be caused by exogenous (Harley et al, 2016;Harper et al, 2010) or endogenous (Willis et al, 2013) factors. We have previously shown that normal CGNP proliferation produces endogenous DNA damage, detectable as small γH2A.X + foci (Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%